EDUCATION OF FUTURE TECHNOLOGICAL EDUCATION TEACHERS FORMING THE SKILLS OF USING TECHNOLOGIES - Nosirov Nodirbek Valijonovich (International Scientific and Current Research Conferences, 2023)
In this article, the method of forming the skills of using educational technologies in future teachers of technological education, the use of active teaching methods in training sessions, the use of technical tools, various independent works of students, Interdisciplinary connections and the analysis of experimental work conducted to determine the formation of technical thinking skills in students are presented.